Climate change reduces warming potential of nitrous oxide by an enhanced Brewer‐Dobson circulation. Issue 11 (4th June 2016) - Kracher, Daniela; Reick, Christian H.; Manzini, Elisa; Schultz, Martin G.; Stein, Olaf
Abstract: The Brewer‐Dobson circulation (BDC), which is an important driver of the stratosphere‐troposphere exchange, is expected to accelerate with climate change. One particular consequence of this acceleration is the enhanced transport of nitrous oxide (N2 O) from its sources at the Earth's surface toward its main sink region in the stratosphere, thus inducing a reduction in its lifetime. N2 O is a potent greenhouse gas and the most relevant currently emitted ozone‐depleting substance. Here we examine the implications of a reduced N2 O lifetime in the context of climate change. We find a decrease in its global warming potential (GWP) and, due to a decline in the atmospheric N2 O burden, also a reduction in its total radiative forcing. From the idealized transient global warming simulation we can identify linear regressions for N2 O sink, lifetime, and GWP with temperature rise. Our findings are thus not restricted to a particular scenario. Key Points: The GWP of N2 O decreases with a decline in the N2 O lifetime under climate change conditions With decreasing lifetime, the total radiative forcing of N2 O is reduced due to a decline in its burden Due to a linear dependence on temperature rise, our findings can be extended to other scenarios